Genetic determinism of fiber type proportion in human skeletal muscle - Simoneau, J. A.; Bouchard, C. (The FASEB Journal, 1995)
Skeletal muscle fiber type distribution is quite heterogeneous, with about 25% of North American Caucasian men and women having either less than 35% or more than 65% of type I fiber in their vastus lateralis muscle. To what extent human skeletal muscle fiber type proportion is under the control of genetic factors is examined in this paper. The results summarized here suggest that about 15% of the total variance in the proportion of type I muscle fibers in human is explained by the error component related to muscle sampling and technical variance, that about 40% of the phenotype variance is influenced by environmental factors, and the remaining variance (about 45%) is associated with inherited factors. These estimates suggest that a difference of about 30% in type I fibers among individuals could be explained exclusively by differences in the local environment and level of muscular contractile activity. However, unidentified genetic factors would have to be invoked to account for the observation that the skeletal muscle of about 25% of the North American Caucasian population have either less than 35% or more than 65% of type I fibers.